Structural and functional effects of histone variant, H2A.Bbd, on the nucleosome core particle - Bao, Yunhe, author; Luger, Karolin, advisor; Anderson, Oren P., committee member; Laybourn, Paul J., committee member; Peersen, Ovle B., committee member; Stargell, Laurie A., committee member (Colorado State University. Libraries, 2005)
In eukaryotic cells, DNA is packaged into a protein-DNA assembly called chromatin. The basic subunit of chromatin is the nucleosome core, which is composed of 147 base pair (bp) of DNA wrapped in 1.65 turns around a histone octamer containing two copies each of the four core histone proteins (H2A, H2B, H3 and H4). Chromatin creates an impediment to the processes of DNA transcription, replication, repair and recombination. In addition to histone covalent modification and ATP-dependent chromatin remodeling, substitution of core histones by the corresponding histone variants plays an important role in transcription regulation in the chromatin context. H2A.Bbd is only 48% conserved compared to major, replication-dependent H2A. Major sequence differences are in the docking domain that tethers the (H2A-H2B) dimer to the (H3-H4)2 tetramer, and in the missing C-terminal region in H2A.Bbd. In this study, several biochemical and biophysical methods were used to investigate the effect of H2A.Bbd incorporation on the structure and stability of nucleosomes. It was found that Bbd-NCP has a more relaxed structure in which only 118+/-2 bp of DNA was protected against digestion with micrococcal nuclease. Furthermore, absence of fluorescence resonance energy transfer (FRET) between the ends of the DNA in Bbd-NCP indicated that the distance between the DNA ends was increased significantly. The Bbd docking domain is largely responsible for this behavior, as shown by domain-swap experiments. Further, it was determined that a hybrid nucleosome, containing an H2A.Bbd-H2B dimer and an H2A-H2B dimer, is formed in vitro. It was found that H2A.Bbd-H2B dimers are easily depleted during in vitro reconstitution. In vitro dimer exchange experiments were used to determine that both conventional and variant histone dimers are more readily exchanged into Bbd-NCPs than into canonical NCPs. These results suggest that incorporation of H2A.Bbd into nucleosomes results in a more open structure and reduced inherent stability. This thesis work sheds light on a cellular mechanism for regulation of transcription, by changing the biochemical makeup of nucleosomes by incorporation of a special histone variant, H2A.Bbd, to reduce the inherent stability of nucleosomes and facilitate transcription.
Keywords: biochemistry; molecular biology; biophysics